ОЦЕНКА МАРКЕРОВ ЭНДОТЕЛИАЛЬНОЙ ДИСФУНКЦИИ У ДЕТЕЙ С ОЖИРЕНИЕМ - Евдокимова, Нина Викторовна; Новикова, Валерия Павловна; Гурина, Ольга Петровна; Блинов, Александр Евгеньевич; Варламова, Ольга Николаевна (FORCIPE, 2022)